Rok 2014 czasem katalońskiego referendum - Hankus, Przemysław (Instytut Studiów Międzynarodowych Uniwersytetu Wrocławskiego, 2014)
The article analyses independence and secessionist aspirations in Europe, with a special focus on the case of Catalonia and the independence referendum that is scheduled to be held by the end of 2014, which according to the Catalonian politicians would become a milestone on the way to Catalonia’s sovereignty, provided the majority will vote for the idea of the Catalonian independent state. Moreover, the author presents and analyses events which led to the passage of the Declaration of Catalonia’s Sovereignty by the Catalonian parliament. Provisions of the Declaration provide for holding an independence referendum in 2014.
Keywords: Katalonia; referendum; niepodległość; secesjonizm; separatyzm